The effects of gut microbiota on metabolic outcomes in pregnant women and their offspring. Issue 9 (13th August 2018) - Lv, You; Yan, Zi; Zhao, Xue; Gang, Xiaokun; He, Guangyu; Sun, Lin; Li, Zhuo; Wang, Guixia
Abstract : Metabolic diseases such as gestational diabetes mellitus and obesity during pregnancy have become severe health issues due to adverse pregnant outcomes in recent years. Abstract : Metabolic diseases such as gestational diabetes mellitus and obesity during pregnancy have become severe health issues due to adverse pregnant outcomes in recent years. Maternal metabolic disorders can influence the long-term health of mothers and their offspring. Current evidence demonstrated that gut microbiota plays a crucial role in metabolic dysfunction during gestation. Maternal status is associated with alterations in the compositions and diversity of the intestinal microbiota community during gestation. Antibiotic treatments may disturb the gut microbiota of pregnant women, and scientific probiotic and prebiotic supplements have positive effects on mothers and their offspring. This review discusses the role of gut microbiota on metabolic outcomes in pregnant women and their offspring, and further illustrates the impact of interventions on metabolic disorders in pregnancy. Our study may provide a novel target for health management during pregnancy.